The Impact of Integrated Evaluation of Hemodynamics on Management of Preterm Infants with Late-Onset Compromised Systemic Circulation - Amer, Reem; Kalash, Reem; Seshia, Mary M.; Elsayed, Yasser N. (American Journal of Perinatology, 2017)
Objectives To study the impact of integrated evaluation of hemodynamics (IEH), using targeted neonatal echocardiography (TNE), cerebral regional tissue oxygenation (crRTO), and fractional oxygen extraction (FOE), using near-infrared spectroscopy (NIRS) on the management of infants with late-onset compromised systemic circulation (LCSC), and evaluation of the hemodynamic characteristics.Study Design Retrospective cohort study comparing infants with LCSC who underwent IEH (April 2014 to May 2016) with an earlier EPOCH who did not undergo IEH (January 2012 to March 2014). The primary outcome was the time to recovery.Results Total 43 infants were included; 18 infants underwent IEH with a median (IQR) 2 (1–3) assessments per infant. The time to recovery was shorter in IEH group with a median (IQR) 28 hours (15–62) compared with non-IEH group 96 hours (30–160). Autoregulation was compromised in 50%, and systemic vascular resistance (SVR) was low in 67%.Conclusion IEH was associated with shorter time to recovery in infants with LCSC.
Keywords: neonatal hemodynamics; targeted neonatal echocardiography; near-infrared spectroscopy; integrated evaluation of hemodynamics